These blue mountains - Thomas, Sarah Loudin (Bethany House Publishers, a division of Baker Publishing Group, 2025)
German pianist Hedda Schlagel's world collapsed when her fiancé, Fritz, vanished after being sent to an enemy alien camp in the United States during the Great War. Fifteen years later, in 1932, Hedda is stunned to see Fritz's name in a photograph of an American memorial for German seamen who died near Asheville, North Carolina. Determined to reclaim his body and bring closure to his ailing mother, Hedda travels to the US. Her quest takes a shocking turn when, rather than Fritz's body, his casket contains the remains of a woman who died under mysterious circumstances. Local deputy Garland Jones thought he'd left that dark chapter behind when he helped bury Fritz Meyer's coffin. The unexpected arrival of Hedda, a long-suffering yet captivating woman, forces him to confront how much of the truth he really knows. As they work together to uncover the identity of the woman in the casket and to unravel Fritz's fate, Hedda and Garland grow closer. But with Hedda in the US on borrowed time while Hitler rises to power in Germany, she fears she'll be forced to return home before she can put the ghosts of her past to rest. --